Bi-Functional Alginate Oligosaccharide-Polymyxin Conjugates for Improved Treatment of Multidrug-Resistant Gram-Negative Bacterial Infections - Joana Stokniene; Lydia C. Powell; Olav A. Aarstad; Finn L. Aachmann; Philip D. Rye; Katja E. Hill; David W. Thomas; Elaine L. Ferguson (MDPI AG, 2020)
The recent emergence of resistance to colistin, an antibiotic of last resort with dose-limiting toxicity, has highlighted the need for alternative approaches to combat infection. This study aimed to generate and characterise alginate oligosaccharide ("OligoG")-polymyxin (polymyxin B and E (colistin)) conjugates to improve the effectiveness of these antibiotics. OligoG-polymyxin conjugates (amide- or ester-linked), with molecular weights of 5200-12,800 g/mol and antibiotic loading of 6.1-12.9% w/w, were reproducibly synthesised. In vitro inflammatory cytokine production (tumour necrosis factor alpha (TNFα) ELISA) and cytotoxicity (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) of colistin (2.2-9.3-fold) and polymyxin B (2.9-27.2-fold) were significantly decreased by OligoG conjugation. Antimicrobial susceptibility tests (minimum inhibitory concentration (MIC), growth curves) demonstrated similar antimicrobial efficacy of ester- and amide-linked conjugates to that of the parent antibiotic but with more sustained inhibition of bacterial growth. OligoG-polymyxin conjugates exhibited improved selectivity for Gram-negative bacteria in comparison to mammalian cells (approximately 2-4-fold). Both OligoG-colistin conjugates caused significant disruption of Pseudomonas aeruginosa biofilm formation and induced bacterial death (confocal laser scanning microscopy). When conjugates were tested in an in vitro "time-to-kill" (TTK) model using Acinetobacter baumannii, only ester-linked conjugates reduced viable bacterial counts (~2-fold) after 4 h. Bi-functional OligoG-polymyxin conjugates have potential therapeutic benefits in the treatment of multidrug-resistant (MDR) Gram-negative bacterial infections, directly reducing toxicity whilst retaining antimicrobial and antibiofilm activities.